Infantile spasms and developmental delay: A case of miller-Dieker syndrome - Jewel Maria George; Carol Sara Cherian; Reji Thomas; Sebin Sunnychan (Wolters Kluwer Medknow Publications, 2023)
Background: Miller-Dieker syndrome (MDS) is a rare genetic disorder, due to contiguous gene deletion on chromosome 17p13.3, characterized by classical type I lissencephaly, severe developmental delay, seizures, cardiac defects, and dysmorphisms. West syndrome is a severe form of epilepsy with epileptic spasms, hypsarrhythmia in electroencephalogram (EEG), and neuropsychomotor delay. Herein, we describe the neurophysiological and neuroimaging findings of a patient with MDS with associated West syndrome. Clinical Description: A 5-month-old boy was brought with new-onset infantile spasms and a history of delay and some regression in milestones. Facial dysmorphism was noted in the form of a prominent forehead, bitemporal hollowing, short nose with upturned nares, thickened upper lip, long philtrum, low-set ears, and hypertelorism. There was hypotonia of all four limbs. Management and Outcome: An EEG showed hypsarrhythmia, and the magnetic resonance imaging brain revealed hypoplastic sulci with pachygyria and smooth cortical surface of supratentorial brain parenchyma - features suggestive of lissencephaly type 1. Echocardiography showed atrial septal defect and minimal pericardial effusion. Whole-exome sequencing showed a contiguous large heterozygous deletion on chromosome 17 which was suggestive of Miller-Dieker lissencephaly syndrome. Parents were counseled, and the spasms were treated with an injection adrenocorticotropic hormone and oral vigabatrin. Conclusion: Structural brain abnormalities are well-known causes of infantile spasms. MDS is a severe malformative condition, lissencephaly being the hallmark of this disorder. This case report will create awareness among pediatricians regarding this rare condition with a characteristic combination of clinical features, which can be confirmed by brain imaging and genetic analysis.